CAD and GIS Integration - Karimi, Hassan A.; Akinci, Burcu (Auerbach Publications, 2009)
Problem solving through CAD and GIS requires a proper integration of these systems for efficient and effective processing of data and operations. Currently, there is no single book that covers the breadth and depth of CAD/GIS integration issues and solutions. This book provides in-depth descriptions of existing and emerging methodologies, techniques, and technologies for integrating CAD and GIS and includes example applications requiring efficient and effective solutions through proper CAD/GIS integration. The text delineates the technical aspects of integrating CAD/GIS, helping readers learn concepts and techniques to analyze, design, and implement projects ranging from the simple to the complex.